Improving Correctional Staff Perceptions of Organizational Justice. Issue 2 (15th March 2023) - Lambert, Eric G.; Lanterman, Jennifer L.; Leone, Matthew; Keena, Linda D.; Haynes, Stacy H.; May, David
ABSTRACT: The current study explored how three key work environment variables – input into decision-making, instrumental communication, and perceived quality of supervision – affected views of distributive and procedural justice among correctional staff ( n = 322) at an unusual Southern prison. Results supported the premise that work environment variables influence the organizational justice perceptions of correctional staff; however, the effects of work environment on organizational justice perceptions differed, as only four of the six hypotheses were supported by the multivariate regression results. Specifically, input into decision-making and quality of supervision had positive effects on both distributive and procedural justice, while instrumental communication did not have a statistically significant relationship with either. The findings indicate that correctional administrators should focus on input into decision-making and quality of supervision in order to increase staff perceptions of organizational justice.